2022
DOI: 10.3390/cells11071168
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cells: Current Literature and Role in Periodontal Regeneration

Abstract: Periodontal disease can cause irreversible damage to tooth-supporting tissues such as the root cementum, periodontal ligament, and alveolar bone, eventually leading to tooth loss. While standard periodontal treatments are usually helpful in reducing disease progression, they cannot repair or replace lost periodontal tissue. Periodontal regeneration has been demonstrated to be beneficial in treating intraosseous and furcation defects to varied degrees. Cell-based treatment for periodontal regeneration will beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 238 publications
(252 reference statements)
0
11
0
Order By: Relevance
“…Nevertheless, the discovery of MSCs from noninvasive sources such as adipose tissue, dental pulp, periosteum, peripheral blood, and umbilical cord provide alternative options for the isolation of MSCs. 14 , 21 , 22 There are also a few potential sites for the isolation of MSCs within the craniofacial region. Accordingly, various types of dental SCs have been isolated, characterised, and studied such as dental pulp SCs (DPSCs), 23 SCs from exfoliated deciduous teeth (SHED), 24 periodontal ligament SCs, 25 SCs from apical papilla, 26 and dental follicle progenitor cells.…”
Section: Sc-based Bone Regenerative Therapymentioning
confidence: 99%
“…Nevertheless, the discovery of MSCs from noninvasive sources such as adipose tissue, dental pulp, periosteum, peripheral blood, and umbilical cord provide alternative options for the isolation of MSCs. 14 , 21 , 22 There are also a few potential sites for the isolation of MSCs within the craniofacial region. Accordingly, various types of dental SCs have been isolated, characterised, and studied such as dental pulp SCs (DPSCs), 23 SCs from exfoliated deciduous teeth (SHED), 24 periodontal ligament SCs, 25 SCs from apical papilla, 26 and dental follicle progenitor cells.…”
Section: Sc-based Bone Regenerative Therapymentioning
confidence: 99%
“…The therapeutic potential of mesenchymal stem cell (MSC)-derived exosomes cannot be overlooked in exosome-related treatment techniques [ 174 , 175 , 176 ]. Human umbilical cord mesenchymal stem cells (hucMSC) have been frequently recognized for their capacity for self-renewal and multilineage differentiation, particularly for the bioactive chemicals they contain for tissue repair and the management of inflammation [ 177 , 178 ]. Han et al discovered that hucMSC-derived exosomes showed a remarkable tissue regeneration potential in rats suffering from traumatic pancreatitis (trauma-induced non-infectious AP) [ 179 ].…”
Section: The Therapeutic Potential Of Exosomes In Ap and Associated Alimentioning
confidence: 99%
“…Studies have attempted to explain why these cells behave a certain way, but many mysteries remain unsolved. The mechanisms of self-renewal, differentiation, and cell proliferation, as well as the underlying signaling pathways, have all been the subject of recent advances in our understanding of the basic biology of these processes (27).…”
Section: Composition Of the Microenvironment In The Spinal Cordmentioning
confidence: 99%